In-patient adult and pediatric vascular ultrasound: Distribution and rate of positive findings. (February 2017) - Lee, Aaron J; Lee, Young; Novak, Daniel; Marks, Natalie; Ascher, Enrico; Hingorani, Anil
Introduction: We examined the rate of positive findings and the distribution of vascular ultrasounds in the pediatric and adult population. Prior literature has noted a low rate of positive findings in adult vascular ultrasounds but there is little literature on pediatric vascular ultrasound. Methods: We reviewed our vascular duplex database on inpatients less than 18 years old and compared it to the adult inpatient vascular duplex exams from 2005 to 2010. Results: The adult patients had more extremity vascular exams while the pediatric patients had more abdominal and renal exams. Moreover, the positive rate of adult lower extremity arterial duplex was significantly higher than the pediatric group ( p  = 0.002). Conclusion: We had a higher yield of positive findings in the adult cases. We observed a higher proportion of more complex duplex exams in the pediatric cases suggesting that a higher level expertise is needed to perform the pediatric vascular duplexes.